Analysis of Application of Accounting Systems and Procedures In Village Fund Management (Case Study of Sukaramai Village, Kec.Sei Balai of Batu Bara Regency) - Ruliana, Ruliana; Nurlaila, Nurlaila; Harahap, Muhammad Ikhsan (Universitas Dehasen Bengkulu, 2023)
This research was conducted with the aim of knowing how to apply accounting systems and procedures that are implemented in the Sukaramai Village office. This research is a qualitative research using a descriptive approach. Data collection techniques used are observation, interviews and documentation. The results of the study show that the accounting systems and procedures for financial management in Sukaramai Village are in accordance with Permendagri Number 20 of 2018. It's just that in the accounting system, Village officials have insufficient human resources, so they experience difficulties managing the accounting system. Then in the accounting procedures at the Sukaramai Village Office there were recording errors in reporting the realization of the 2020 budget. Even though the Village had attended training held both from the District and from the Regent the Village apparatus still experienced difficulties in terms of the accounting system. Even so, the Sukaramai Village officials are still trying and trying to work optimally.